2003
DOI: 10.1046/j.1523-1755.64.s87.22.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of bioelectrical impedance parameters to nutrition and survival in peritoneal dialysis patients

Abstract: Relationship of bioelectrical impedance parameters to nutrition and survival in peritoneal dialysis patients.Background. Malnutrition is highly prevalent in peritoneal dialysis (PD) patients and is associated with higher mortality in these patients. In this study, we have prospectively examined the relationship of bioimpedance indexes to the nutritional status and survival in PD patients.Methods. We enrolled 48 PD patients beginning in November 2000. On enrollment, bioelectrical impedance analysis (BIA) (BIA-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 18 publications
1
84
0
7
Order By: Relevance
“…A positive correlation between creatinine and PA has been previously reported 18,19 and supports the value of PA as a nutritional marker, particularly of muscle mass. Consistent with Mushnick et al 20 worse survival was also observed among our patients with PA < 6° according to univariate analysis.…”
Section: Discussionsupporting
confidence: 92%
“…A positive correlation between creatinine and PA has been previously reported 18,19 and supports the value of PA as a nutritional marker, particularly of muscle mass. Consistent with Mushnick et al 20 worse survival was also observed among our patients with PA < 6° according to univariate analysis.…”
Section: Discussionsupporting
confidence: 92%
“…[10][11][12] Moreover, phase angle appears to reflect prognosis in populations with chronic disease. [13][14][15][16][17][18] Whether phase angle is associated with frailty and mortality in the general population is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Phase angle has been shown to be predictive of survival in dialysis population [21]. We have demonstrated that newer normalized bioimpedance parameters have better survival predictive value compared to phase angle [10].…”
Section: Discussionmentioning
confidence: 78%